Communists, Commissars, and Consumers: The Politics of Food on the Chilean Road to Socialism. - Frens-String, Joshua (Hispanic American Historical Review, 2018)
This article examines the politics of food during Chile's Popular Unity (UP) revolution (1970--73). Organized around the rise and fall of the Juntas de Abastecimiento y Precios (Price and Supply Committees, JAPs), a state-backed network of collectively managed stores and ad hoc food distribution sites, the article explores how the UP revolution expanded long-standing practices of community-led price monitoring and food distribution to make the promise of economic democracy more concrete for urban, working-class consumers. As the JAPs' power grew, however, such efforts became a political lightning rod, unifying Chile's domestic opposition around the claim that the state's presence in the food economy--rather than its absence--created scarcity and needlessly politicized domestic life. Ultimately, the article contends that the consumer marketplace was a key arena for competing conceptualizations of democracy and the state in early 1970s Chile, anticipating the centrality of consumption to the neoliberal counterrevolution that the country experienced in the post-UP era.